2013
DOI: 10.1364/josab.30.002326
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling and determination of limiting powers for volume Bragg gratings used in lasers for spectral control

Abstract: In this paper we present a model to investigate the thermal limitations of volume Bragg gratings (VBGs) used in lasers for spectral control. Also presented are the limiting optical powers, to which intracavity VBGs of different length could be subjected, before the laser operation rapidly deteriorates. The results revealed that the power limit of a VBG-locked laser is highly dependent on the length of the employed VBG. Furthermore, the power limit expressed in incident power related linearly to the radius of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We chose this cavity design to avoid having the passive Q-switch exposed to pump light, to get flexibility in choosing the intensity on the Q-switch and at the same time getting a large mode size at the VBG. The latter is important as it has been previously shown that there is a limit to the amount of power a VBG can be exposed to without a decrease in its diffraction efficiency [20,21], and this limit increases linearly with the mode radius [22]. The gain medium was a 1.5-mm-long, Ng-cut Yb:KYW crystal with 5 at.% Yb-doping and both endsurfaces AR-coated for pump and emission wavelengths.…”
Section: Resultsmentioning
confidence: 99%
“…We chose this cavity design to avoid having the passive Q-switch exposed to pump light, to get flexibility in choosing the intensity on the Q-switch and at the same time getting a large mode size at the VBG. The latter is important as it has been previously shown that there is a limit to the amount of power a VBG can be exposed to without a decrease in its diffraction efficiency [20,21], and this limit increases linearly with the mode radius [22]. The gain medium was a 1.5-mm-long, Ng-cut Yb:KYW crystal with 5 at.% Yb-doping and both endsurfaces AR-coated for pump and emission wavelengths.…”
Section: Resultsmentioning
confidence: 99%